Water permeability is a measure of severity in acute appendicitis - Nicola Pini; Viktoria A. Pfeifle; Urs Kym; Simone Keck; Virginie Galati; Stefan Holland-Cunz; Stephanie J. Gros (Taylor & Francis Group, 2017)
Acute appendicitis is the most common indication for pediatric abdominal emergency surgery. Determination of the severity of appendicitis on clinical grounds is challenging. Complicated appendicitis presenting with perforation, abscess or diffuse peritonitis is not uncommon. The question remains why and when acute appendicitis progresses to perforation. The aim of this study was to assess the impact of water permeability on the severity of appendicitis. We show that AQP1 expression and water permeability in appendicitis correlate with the stage of inflammation and systemic infection parameters, leading eventually to perforation of the appendix. AQP1 is also expressed within the ganglia of the enteric nervous system and ganglia count increases with inflammation. Severity of appendicitis can be correlated with water permeability measured by AQP1 protein expression and increase of ganglia count in a progressive manner. This introduces the question if regulation of water permeability can present novel curative or ameliorating therapeutic options.